State-prioritised heritage: governmentality, heritage management and the prioritisation of the liberation heritage in post-colonial South Africa - Manetsi, Thabo (African Studies, 2018)
This study seeks to examine and trace the notion of state prioritisation of heritage in relation to state intervention through political, policy and governance regimes in heritage management in South Africa. The study covers key highlights in the evolution of heritage management and developments through specific epochs and contexts such as the colonial, apartheid and post-colonial South Africa. Drawing on theories such as 'governmentality' and 'authorised heritage discourse' the study provides a perspective on the extent of state influence and dominance in the formalisation of heritage management through policy, legal instruments and governance processes. Using the National Liberation Heritage Route project in South Africa as a case study, the research illustrates the notion of state prioritisation of heritage in relation to the deployment and mobilisation of state resources (policy, legal instruments and material resources) in heritage management to support a select past as 'official' heritage of the nation state. The politics of transforming the heritage landscape in post-1994 South Africa witnessed the emergence of the idea of state prioritisation of the liberation heritage as a site for restorative justice particularly to honour and recognize the legacy of the political struggles for freedom against colonialism and apartheid. Conversely, the framing of the liberation heritage also demonstrates political uses of heritage at expedient moments to achieve political goals by the regime in power and state control. While normative approaches to heritage management tend to emphasise the disjuncture between colonial and post-colonial periods, the results of this study confirm strong ties to colonial and European influences across these categories. The findings outline the complexity of state intervention and its inherent biases that inform the governance of heritage. In this light the study contributes to ongoing research on the discourse of evaluating the global, local, and transnational dimensions of heritage management and practices, in relation to the problematics of heritage as mainly a product of state authority and political power.